Development and implementation of a T-RFLP procedure for use on bioreactor sludge - Tan, Daniel Chiao Thien (2013)
Terminal restriction fragment length polymorphism analysis is popularly used as fast and reliable method to investigate the profile of microbial communities in environmental samples. It can be used as a fingerprinting technique to investigate the structure and composition of bacteria that are present in the wastewater treatment processes. In this project, I developed a T-RFLP method for wastewater sludge and used this method to investigate the bacterial community in sludge from four membrane bioreactors. DNA extracted from bioreactor sludge samples underwent Polymerase Chain Reaction to amplify the 16S rRNA gene; this amplicon then underwent PCR product purification, and the purified amplicon was finally enzyme digestion whereby a variety of enzymes were used to obtain Terminal-Restriction Fragments. A major portion of the project involved optimization of these steps in the T-RFLP pipeline. Data analysis was then done to identify which enzyme gave the most number of true peaks and highest fluorescence. This T-RFLP pipeline was used to examine the microbial diversity of sludge in four MBRs and the communities were compared quantitatively using three diversity indices, namely richness, dynamics and evenness. The optimized procedure developed in my project will also continue to be used as the standard T-RFLP protocol in the Experimental Bioprocess Evolution group at Singapore Centre of Environmental Life Sciences Engineering (SCELSE).